Physical, mechanical, and combustion properties of twelve wood species from the Brazilian Amazon - Carbonato de Souza, Leandro Vinicius; Zanatta, Bruno; Siqueira, Adriano; Corradi Pereira, Bárbara Luísa; Lengowski, Elaine Cristina; Oliveira, Aylson Costa (Maderas. Ciencia y Tecnología, 2024)
Studying the combustibility and physical‒mechanical properties of wood is important for recommending its use in construction. The objective of this study was to evaluate the combustibility, as well as the physical and mechanical properties, of twelve Brazilian Amazonian woods. Species. For each species, the combustibility parameters, fire exposure test, residual mass, loss mass, intact mass, charred area, proximate analysis, basic density, compressive strength and modulus of elasticity were determined. All the evaluated properties were significant affected by the wood species. In the fire exposure test, ignition time ranged from 21 s to 55 s while flame time was between 108 s and 233 s. Residual mass ranged from 60,7% to 82,7%, and intact areas ranged from 28,13 % to 62,68 %. Basic density values ranged from 335 kg/m3 to 889 kg/m3, compressive strength ranged from 29 MPa to 82 MPa, and the modulus of elasticity ranged from 9 GPa to 33 GPa. The wood of Hymenaea courbaril (courbaril), Manilkara huberi (masaranduba), Handroanthus serratifolius (yellow lapacho) was identified as the most suitable for structural components, ensuring greater safety against possible fires. Short-term fire exposure tests, particularly the ignition time parameter combined with residual mass and intact area, are key for assessing wood resistence to fires.